2019
DOI: 10.1097/bpo.0000000000001386
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Meniscus Tears

Abstract: Background: In order to determine whether treatments are effective in the treatment of meniscus tears, it is first necessary to understand the natural history of meniscus tears. The purpose of this paper is to review the literature to ascertain the natural history of meniscus tears in children and adolescents. Methods: A search of the Pubmed and Embase databases was performed using the search terms "meniscus tears," "natural history of meniscus tears," "knee meniscus," "discoid meniscus," and "natural history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 26 publications
1
29
0
1
Order By: Relevance
“…The incidence of meniscal injuries is on the rise, which might be partly attributed to the general aging of the population [23]. Previous studies have found that age-related meniscus denaturation induces an increase in fragility of meniscus tissue, thereby increasing the incidence of meniscus tearing in the elderly population [24].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of meniscal injuries is on the rise, which might be partly attributed to the general aging of the population [23]. Previous studies have found that age-related meniscus denaturation induces an increase in fragility of meniscus tissue, thereby increasing the incidence of meniscus tearing in the elderly population [24].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of meniscal injuries is on the rise, which might be partly attributed to the general aging of the population [30]. Previous studies have found that age-related meniscus denaturation induces an increase in fragility of meniscus tissue, thereby increasing the incidence of meniscus tearing in the elderly population [31].…”
Section: Discussionmentioning
confidence: 99%
“…18 29 30 38-40 We did not find any report describing a specific mechanism of injury for discoid meniscal tears, as the true natural history of discoid menisci is still thought to be unknown. 41…”
Section: Mechanism Of Injurymentioning
confidence: 99%